Powdery Mildew-Induced Mla mRNAs Are Alternatively Spliced and Contain Multiple Upstream Open Reading Frames - Halterman, Dennis A. (American Society of Plant Biologists, 2003)
In barley (Hordeum vulgare), the Mla13 powdery mildew resistance gene confers Rar1-dependent, AvrMla13-specific resistance to Blumeria graminis f. sp. hordei (Bgh). We have identified cDNA and genomic copies of Mla13 and used this coiled-coil nucleotide-binding site leucine-rich repeat protein-encoding gene as a model for the regulation of host resistance to obligate biotrophic fungi in cereals. We demonstrate quantitatively that a rapid increase in the accumulation of Mla transcripts and transcripts of the Mla-signaling genes, Rar1 and Sgt1, is triggered between 16 and 20 h post inoculation, the same time frame that haustoria of avirulent Bgh make contact with the host cell plasma membrane. An abundance of Mla13 cDNAs revealed five classes of transcript leader regions containing two alternatively spliced introns and up to three upstream open reading frames (uORFs). Alternative splicing of introns in the transcript leader region results in a different number of uORFs and variability in the size of uORF2. These results indicate that regulation of Mla transcript accumulation is not constitutive and that induction is coordinately controlled by recognition-specific factors. The sudden increase in specific transcript levels could account for the rapid defense response phenotype conferred by Mla6 and Mla13.